2004
DOI: 10.1074/jbc.m407986200
|View full text |Cite
|
Sign up to set email alerts
|

Association of γ-Secretase with Lipid Rafts in Post-Golgi and Endosome Membranes

Abstract: Alzheimer's disease-associated ␤-amyloid peptides (A␤) are generated by the sequential proteolytic processing of amyloid precursor protein (APP) by ␤-and ␥-secretases. There is growing evidence that cholesterol-and sphingolipid-rich membrane microdomains are involved in regulating trafficking and processing of APP. BACE1, the major ␤-secretase in neurons is a palmitoylated transmembrane protein that resides in lipid rafts. A subset of APP is subject to amyloidogenic processing by BACE1 in lipid rafts, and this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
369
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(395 citation statements)
references
References 76 publications
22
369
2
Order By: Relevance
“…The nicastrin and PS1 antisera used in the present study have been previously characterized [29,30,51]. The specificity of antisera is further confirmed by our immunoblotting experiment, which showed that nicastrin antiserum essentially reacted with one major band of approximately 120 kDa corresponding to the mature complex glycosylated forms of the protein in all brain regions examined.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The nicastrin and PS1 antisera used in the present study have been previously characterized [29,30,51]. The specificity of antisera is further confirmed by our immunoblotting experiment, which showed that nicastrin antiserum essentially reacted with one major band of approximately 120 kDa corresponding to the mature complex glycosylated forms of the protein in all brain regions examined.…”
Section: Discussionsupporting
confidence: 70%
“…In parallel, four rats from each of the following postnatal developmental stages i.e., P1, P7 and P21 were decapitated and brain regions of interest (i.e., cortex, hippocampus, cerebellum and brainstem) were dissected out and homogenized in Tris-lysis buffer. Tissues were then processed for immunoprecipitation by incubating with SP718 nicastrin antiserum as described earlier [30,51]. The immune complexes were precipitated by protein A/G PLUS-agarose, separated by 4-20% polyacrylamide gel electrophoresis for 90 min before being transferred to PVDF membranes.…”
Section: Immunoblottingmentioning
confidence: 99%
“…Intriguingly, cellular phenotypes in PIP 2 -compromised cells are reminiscent of those observed in cells expressing FADassociated presenilin mutations, e.g., ion channel and trafficking deficits (15). The potential role of presenilin in PIP 2 metabolism can be further evidenced by occurrence of PS1 in PIP 2 -enriched subcellular compartments, including lipid rafts (44), phagocytic cups (19), lamellipodia (45), and adherent junctions (18). Thus, our study raises the possibility that PIP 2 may play a key role in the multiple cellular defects associated with presenilin FAD mutations.…”
Section: Discussionmentioning
confidence: 88%
“…DHA, from which 19,20-DHDP is derived, is particularly interesting in this respect as it tends to incorporate more readily into lipid rafts than EPA (Williams et al, 2012). Changes in the lipid composition of the plasma membrane can have marked consequences of the formation and stability of the -secretase complex (Vetrivel et al, 2004;Vetrivel and Thinakaran, 2010). We found that 19,20-DHDP, but not the corresponding epoxide, altered cholesterol distribution in cellular membranes and displaced presenilin 1 from lipid rafts, where the processing of substrate proteins preferentially occurs, to non-raft fractions, thus disrupting the -secretase complex.…”
Section: Methodsmentioning
confidence: 99%
“…The -secretase complex is made up of several proteins, including presenilin 1, nicastrin, anterior pharynx defective 1, and presenilin enhancer 2, and the active complex is localized to lipid rafts (Vetrivel et al, 2004;Hur et al, 2008;Vetrivel and Thinakaran, 2010). We therefore determined whether 19,20-DHDP could inhibit the -secretase by altering the localization of constituent proteins and concentrated on presenilin 1.…”
Section: Downloaded Frommentioning
confidence: 99%